Study of Health Behaviors Regarding Food Consumption Behavior among Students of Princess of Naradhiwas University - Promthongdee, Chanita; Juychum, Detdanai; Kamhaengkit, Rojarek; Aroonjit, Nualprang (Princess of Naradhiwas University Journal, 2025)
This research aimed to: 1) examine health behaviors and food consumption behavior; 2) determine the relationship between health behaviors and food consumption behavior among 354 students of Princess of Naradhiwas University throughout the academic year 2024. Research instruments were health behavior questionnaire and food consumption behavior of students that had the overall Alpha Cronbach’s coefficient was 0.801. The content validity of health behavior equaled 0.830 and food consumption behavior equaled 0.706. Data was analyzed by using average, percentage, standard deviation, coefficient of variation, skewness, kurtosis, and Pearson Correlation Coefficient. The research results found that: 1) students had moderate health behaviors were at the highest level (57.63 %), moderately risky sweet food consumption behaviors were at the highest level (62.43%), high risk fatty food consumption behaviors were at the highest level (75.70 %), and high risk sodium food consumption behaviors were at the highest level (61.30%); and 2) There was a low level of positive correlation between health behaviors and sweet food consumption behaviors (r = 0.106), a low level of negative correlation with fatty food consumption behaviors (r = -0.110), and a low level of negative correlation with sodium food consumption behaviors (r = -0.122).